ANALISA RESIDU PESTISIDA DI WILAYAH MALANG DAN PENANGGULANGANYA UNTUK KEAMANAN PANGAN BUAH JERUK - Astri Sumiati; Reza Prakoso Dwi Julianto (Universitas Tribhuwana Tunggadewi, 2018)
The use of pesticides is widely used in the production of citrus fruits for protection before and after harvest. The use of pesticides on a broad scale can pollute the environment and leave residues in plants and in plants such as fruit leaves and tubers. A survey was conducted to evaluate the level of pesticide residues in citrus fruits. The survey method is carried out by recording pesticide use by farmers and traders. The survey will be conducted in Dau, Batu and Poncokusumo Districts, Malang Regency by interviewing 10 farmers and 10 orange traders in each District. The Gas Cromatography method was carried out to measure the levels of pesticide residues tested at the Angler Biochemlab Laboratory, Surabaya. Descriptive analysis was used to analyze the levels of pesticide residues in citrus fruits then compared to the Maximum Residue Limit (BMR) through SNI 7313: 2008 quality standards on agricultural products. The residue levels of profenofos in farmer samples were found to be higher at 0.108 ppm compared to the sample from traders, namely 0.050 ppm at the Tegalweru village research site. In addition, traders in the village of Poncokusumo knew the imidaclroripid content was close to the maximum threshold of 0.040 ppm in farmer samples and 0.010 ppm in the merchant sample. Decreased levels of pesticide residues on food can be done with several approaches, namely physically and chemically. Reduction of pesticide residues in agricultural products can be done in several ways including by washing products with running water for several times or can also be done by soaking in water for one hour